Zakat Distribution Role in Reducing People Poor Number in Semarang City - Nura Yuli Fadhilahningrum; Karsinah Karsinah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Poverty is one of the main problems facing Indonesia to date, as the capital of Central Java City Semarang also can not be separated from this poverty problem. Although the number of poor people from year to year decline, but in terms of proportion to the total population of Semarang City, the number of poor people reached 20%. One instrument that can help reduce poverty is zakat. This study aims to analyze the impact of zakat as poverty reduction with zakat approach and with zakat. The analytical tool used in this research is poverty indicator consisting of headcount ratio, poverty gap index, income index gap, Sen index and FGT (Foster, Greer, Thorbecke) index and CIBEST Index. The find show that zakat can reduce the poverty rate and also can improve the level of welfare of a family, both material and spiritual.